Pengelolaan Administrasi Sekolah di MI Jayasari - Arlan Hidayatulloh; Dede Asiah; Irfan Afandi; Pipin Pitriyani; Rama Aditya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
In the implementation of education, good school administration management is needed to be able to provide services to related parties to produce better performance. Accuracy, accuracy and speed of data/information presentation are important factors in managing good administration. One of the tasks of school administration staff in an educational institution is in terms of correspondence, because of that school administration is often called writing work which produces letters and then collects them into archives. The management of correspondence needs to be applied to each educational institution, because it is a source of data or information that is useful for the maximum progress of the educational institution, the source of data and information used is in the form of a letter document.